Role of cytosolic calcium and actin polymerization on agonist-induced secretion by the platelets of liver cirrhosis patients - Sam Annie-Jeyachristy; Arumugam Geetha; Rajagopal Surendran; Subburayan Jeevan Kumar; Sarangapani Arulprakash (Turkish Journal of Hematology, 2009)
Objective: Variceal bleeding in cirrhosis is mainly due to platelet activation defect and secondary to coagulation defects. Secretion is an important process which release procoagulants for hemostasis. In the present investigation we have evaluated the secretory function of platelets in liver cirrhosis and also the simultaneous changes in cytosolic calcium (Ca2+) and the polymerization of actin in agonist- stimulated platelets in vitro.Methods: Liver cirrhotic patients with (n=27) or without (n=23) bleeding complication were included in the study. Control subjects (n=50) were also utilized for the study to compare the analytical data. Platelets were activated by collagen in vitro and the secretory response was assessed by the levels of nucleotides, serotonin, pyrophosphate (PPi) and inorganic phosphate (Pi) secreted into the extracellular fluid of the platelet suspension at various time intervals. During the course of secretion the alteration in the polymerization of actin was monitored simultaneously with the changes in the cytosolic Ca2+ level.Results: The secretory response of platelets to collagen was significantly low in both bleeders and non-bleeders when compared to that of normal subjects. During secretion, low level of actin polymerization and cytosolic Ca2+ level were observed in the platelets of bleeders than in non-bleeders and normal subjects. The low secretory capacity of cirrhosis platelets could be correlated with low levels of actin polymerization and cytosolic Ca2+. The alterations were highly significant in the platelets of bleeders when compared to those of non-bleeders. Conclusion: The defective secretory activity of platelets in cirrhosis bleeders might be partly due to low polymerization of G-actin to F-actin which is required for platelet shape change and for the release of procoagulants. Cytosolic Ca2+ level seems to influence actin polymerization and thereby impairs platelet secretory response to agonists in cirrhosis patients with bleeding complication.